The thnRDE operon from B. thuringiensis provides immunity to Lactococcus lactis against thurincin H - Núñez Valle, Mario Alberto; Velázquez Juárez, Gilberto; Barboza Corona, José Eleazar; Casados Vázquez, Luz Edith (Acta Universitaria, 2022)
Lactococcus lactis is a lactic acid bacterium of great importance for the food industry. Due to L. lactis safety status, systems have been designed for the expression of recombinant proteins of biotechnological interest. A peptide with biotechnological importance is the bacteriocin thurincin H, which has many favorable characteristics to be used as a bioconservative in food. It has been reported that it needs at least nine genes for its biosynthesis, within these, the thnRDE genes provide immunity to the native producer strain. The objective of this work was to integrate these genes into the L. lactis strain to make it resistant to thurincin H and to be able to produce it in the future. To achieve this, the thnRDE genes were cloned into a vector for L. lactis and transformed into the sensitive strain. It was possible to obtain a strain of L. lactis resistant to thurincin H that can be used for its safe heterologous production.